Mapping Out Taiwan-Indonesia Bilateral Cooperation: Establishing Interdependence on People-to-People Connectivity - Melkis, Juan Carlos; Alam, Gilang Nur; Dermawan, Windy (Indonesian Journal of Social Science Research, 2025)
This study explores Taiwan-Indonesia bilateral cooperation strategies in fostering interdependence through people-to-people connectivity during 2016–2024, influenced by Taiwan's New Southbound Policy. Using a qualitative descriptive approach and secondary data, the research highlights Taiwan's initiatives, including scholarship programs, visa facilitation, Muslim-friendly tourism promotion, and protections for Indonesian migrant workers. These efforts have strengthened social, cultural, and educational ties between the two nations. The findings show that these strategies significantly enhance bilateral relations, offering Indonesia opportunities for human resource development and improved migrant worker welfare, while Taiwan deepens its connectivity with a key ASEAN partner. Despite these advancements, Indonesia's adherence to the One China Policy imposes diplomatic constraints, limiting formal interactions and collaborations. The study concludes that people-to-people connectivity is a vital component of Taiwan-Indonesia bilateral relations, fostering mutually beneficial interdependence. It recommends further policy innovations to enhance social and cultural exchanges, ensuring the sustainability of bilateral collaboration.